Molecular mechanisms of anticancer activities of polyphyllin VII. (7th January 2021) - Ahmad, Bashir; Rehman, Shafiq Ur; Azizullah, Azizullah; Khan, Muhammad Fiaz; Din, Syed Riaz Ud; Ahmad, Manzoor; Ali, Ashraf; Tahir, Naeem; Azam, Nasir; Gamallat, Yaser; Rahman, Khalil Ur; Ali, Muhsin; et al.
Abstract: Cancer is the leading cause of mortality in the world. The major therapies for cancer treatment are chemotherapy, surgery, and radiation therapy. All these therapies expensive, toxic and show resistance. The plant‐derived compounds are considered safe, cost‐effective and target cancer through different pathways. In these pathways include oxidative stress, mitochondrial dependent and independent, STAT3, NF‐kB, MAPKs, cell cycle, and autophagy pathways. One of the new plants derived compounds is Polyphyllin VII (PPVII), which target cancer through different molecular mechanisms. In literature, there is a review gap of studies on PPVII; therefore in the current review, we summarized the available studies on PPVII to provide a base for future research. Abstract : Cancer is the leading cause of mortality in the world. The major therapies for cancer treatment are chemotherapy, surgery and radiation therapy. All these therapies expensive, toxic and show resistance. The plant derived compounds are considered safe, cost effective and target cancer through different pathways. In these pathways include, oxidative stress, mitochondrial dependent and independent, STAT3, NF‐kB, MAPKs, cell cycle and autophagy pathways. One of the new plants derived compounds is Polyphyllin VII (PPVII), which target cancer through different molecular mechanisms. In literature, there is a review gap of studies on PPVII, therefore in the current review; we summarized the available studies on PPVII to provide a base for future research.